1998
DOI: 10.1046/j.1525-1497.1998.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of domestic violence in an inpatient female population

Abstract: Studies have evaluated the prevalence of domestic violence in populations of patients in emergency and primary care settings, but there are little data on patients admitted to hospitals. We undertook a study to evaluate the prevalence of domestic violence among female inpatients. Of 131 consecutive female patients between the ages of 18 and 60 admitted to a nontrauma urban teaching hospital asked to complete a self-administered survey about domestic violence, 101 completed the questionnaire. Twenty-six percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The high prevalence of this phenomenon has given rise to an increasing number of publications on DV and IPV, regarding the signs, symptoms, diagnosis [5][6][7] and even the medical-professional role in the treatment and guidance of the survivors [8]. IPV has profound health consequences: abused women are more likely to have physical and psychological problems, including reproductive problems, depression, psychosomatic disorders, and limitations in social functioning [9].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of this phenomenon has given rise to an increasing number of publications on DV and IPV, regarding the signs, symptoms, diagnosis [5][6][7] and even the medical-professional role in the treatment and guidance of the survivors [8]. IPV has profound health consequences: abused women are more likely to have physical and psychological problems, including reproductive problems, depression, psychosomatic disorders, and limitations in social functioning [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lifetime prevalence of domestic violence was 20% in a nationally representative survey in the United States (US), 1 compared with 26% for hospitalised women. 2 Furthermore, 51% of women attending an outpatient clinic 3 reported having experienced domestic violence. In studies done using data from hospital emergency departments in the US, lifetime prevalence of domestic violence has varied from 33% to 54%.…”
mentioning
confidence: 99%
“…To the best of our knowledge, the only study presenting IPV prevalence data in patients hospitalized for other than psychiatric problems was performed by McKenzie and colleagues 18 in 1997. In their group of 130 patients (61 on internal medicine, 59 on surgery, 7 on obstetrics, and 3 on psychiatry), the 1-year and lifetime prevalences of IPV were only 5% and 26%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5,10,[12][13][14] Although reports indicate that victims of IPV are more likely to be hospitalized, [15][16][17] the only study assessing the prevalence of IPV in hospitalized patients included women on medical, surgical, and obstetrical services and reported 1-year and lifetime prevalences of only 5% and 23%, respectively. 18 We hypothesized that the prevalence of IPV in hospitalized patients would be at least as high as that reported from emergency departments and sought to measure the 1-year and lifetime prevalences of IPV in women admitted to a general internal medicine service. In addition, because studies done in various outpatient settings have reported that victims of IPV have a variety of somatic complaints and an increased prevalence of chronic and functional illnesses, [19][20][21][22][23] we also sought to determine whether women with a history of IPV and women without a history of IPV had different numbers or types of positive responses to questions asked on the review of systems.…”
mentioning
confidence: 99%